Fundamental Analysis to Assess The Fair Price of PT. Antam Tbk. Shares - Astriwati Biringkanae; Dedy Wanli (Universitas Kristen Indonesia Toraja, 2022)
The purpose of this study was to deterrmine the price of shares in PT Antam Tbk. as a reference to determine the fair price of shares of PT. Antam on the Indonesian share exchange. Fundamental analysis is a method used to determine whether the share price on the Indonesian share exchange is already appropriate to the company's intrinsic value. The research method uses a quantitative descriptive approach, namely analyzing and processing numerical data obtained from the official website of the Indonesian share exchange to determine the level of fairness of the share price of PT Antam Tbk. Price Earning Ratio in the period 2020-2022 of PT. Antam Tbk. has increased and Price Book Value in the period 2020-2022 of PT Antam Tbk. is at a fair share price value position (undervalued).